Contribution à l’anthropologie de la consommation de champignons à partir du cas du sud-ouest de la France (xvie-xxie siècles) - Frédéric Duhart (Revue d'ethnoécologie)
The study of mushroom consumption offers an interesting contribution to the understanding of the relations between the societies and the potential foods that they can find in their environment. Evoking the mushroom consumption by the South-West France populations leads first to think about the classification of living things, the social building of edibility and the dynamics of these processes. Once the « edible » mushrooms identified, we have to note the complexity and the variability of the gastronomic hierarchies and the diversity of mushroom consumption contexts. Some species were soon widely appreciated and got early an important commercial value. The history of their trade and consumption invite to think about the management of a « natural resource ». This paper is the fruit of a longue durée approach to mushroom consumption in South West France. A part of the material used in this study consists of contemporary observations and interviews. Another consists of documents classically ignored or underexploited by French historians. Not toxic and toxic species evoked in this work: Agaricus campester, A. bisporus, Amanita caesarea, A. muscaria, A. ovoidea, A. phalloides, A. strobiliformis, A. verna, Armillaria mellea, Boletus aereus, B. aestivalis, B. badius, B. edulis, B. pinophilus, Calocybe gambosa, Cantharellus cibarius, C. lutescens, C. tubeaformis, Coprinus atramentarius, C. comatus, Cortinarius splendens, Entoloma sepium, E. clypeatum, Hydnum repandum, Lactarius deliciosus, Leccinum aurantiacum, Lepiota procera, Marasmius oreades, Mitrophora semilibera, Morilla esculenta, Pleurotus eryngii, Russula virescens, Terfezia leptoderma, Tricholoma auratum, T. myomyces, T. portentosum, Tuber borchii, T. melanosporum and Ustilago maydis.